Computational Fluid Dynamics of Human Cerebral Circulation- A Study of Shear Stress in the Circle of Willis with and without Constructed Aneurysms - Abass, Amir; Andersson, Carl; Berggren, Henrik; Ahlgren, Kajsa; Ignell, Victoria; Koivistoinen, Vilma (My University, 2019)
A cerebral aneurysm is a local enlargement of a weakened blood vessel wall in the brain. It is a critical condition that causes several deaths yearly due to the fatal intracranial bleeding that a rupture of an aneurysm can cause. This report investigates aneurysms with focus on their impact on shear stress in blood vessels where aneurysms are often found. This is done with the aim to gain further knowledge about the correlation between mechanical factors and aneurysm progression. Throughout the report images of brains from two healthy patients, taken with magnetic resonance imaging, serve as a fundamental basis of real-world representation of blood vessels in the human brain. The scanned images were reconstructed into three-dimensional volumetric data to use for simulations. A total of seven specific vascular geometries were chosen from the two brains. All were selected in the Circle of Willis, a specific section in the lower central part of the brain. The Circle of Willis is a domain particularly prone to the development of aneurysms. Since the images originated from healthy patients the chosen geometries did not contain any aneurysms. Therefore a modified copy of each selected geometry was created as well, with the difference being that they contained a virtually inserted aneurysm. The blood flow of the reconstructed vascular geometries was computed and simulated using the Lattice Boltzmann method. It is a numerical method that recovers the Navier-Stokes continuity and generates the velocity field within the chosen blood vessel geometries. The blood flow was simulated in all seven pairs of blood vessels. With the acquisition of the velocity distribution within the vessel, the corresponding distribution of shear stress was calculated. Results from the simulations were compared between the cases with and without aneurysm with respect to shear stress. The concluding result was that a global increase in shear stress was found for the geometries with an aneurysm. This result suggests that the progression of one aneurysm could lead to a weakened blood vessel that is likely to develop an increased number of aneurysms.
Keywords: Lattice Boltzmann, Cerebral aneurysm, Cerebral circulation, CFD, Vascular system